2006
DOI: 10.1007/bf03395546
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Retention of Olfactory Discrimination Learning Set in Rats

Abstract: Six male Sprague-Dawley rats were used to examine the long-term retention of an olfactory discrimination learning set. Rats were trained on 30 odor-unique, 5-trial discrimination problems, transferred to an olfactory discrimination reversal task, and then given a 6-week break in training. The rats demonstrated use of a learning set by performing significantly bettE3r than expected by chance on Trial 2 on both the olfactory discrimination problems and the olfactory discrimination reversal problems. Following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…Although we could not show that dwarf goats were performing well on Trial 4 as in classical experiments investigating the learning set phenomenon (because of statistical reasons related to the criterion method)—they are still showing an increased efficiency to solve these problems indicating an improvement in performance (i.e., that they are learning to learn). It is quite possible that the goats may need more than nine problems to show a high percent correct on Trial 4 (, e.g., with two-choice discrimination tasks, rats generally need at least 10 problems before showing a significantly better than chance performance on Trial 2; e.g., Bailey, 2006; Bailey & Thomas, 2001). We concluded that their cognitive ability is equivalent to level five in Thomas's Hierarchy of Types of learning (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not show that dwarf goats were performing well on Trial 4 as in classical experiments investigating the learning set phenomenon (because of statistical reasons related to the criterion method)—they are still showing an increased efficiency to solve these problems indicating an improvement in performance (i.e., that they are learning to learn). It is quite possible that the goats may need more than nine problems to show a high percent correct on Trial 4 (, e.g., with two-choice discrimination tasks, rats generally need at least 10 problems before showing a significantly better than chance performance on Trial 2; e.g., Bailey, 2006; Bailey & Thomas, 2001). We concluded that their cognitive ability is equivalent to level five in Thomas's Hierarchy of Types of learning (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Para isso, o autor estabeleceu um procedimento em seis partes: 1) treino de acesso ao bebedouro; 2) pré-teste da tarefa final; 3) treino do operante de empurrar o cubo; 4) teste intermediário de recombinação com um comportamento adquirido; 5) treino do operante de subir no cubo e erguer-se; 6) teste final de recombinação. (Jennings & Keefer, 1969;Slotnick & Katz, 1974;Slotinick, Hanford & Hodos, 2000;Bailey, 2006). Por exemplo, as únicas demonstrações de learning set em ratos têm sido obtidas quando estímulos olfativos foram utilizados no treino discriminativo (Bailey, 2006;Slotnick, Hanford & Hodos, 2000 (Epstein et al, 1984) e ratos (Delage, 2006;Tobias, 2006;Ferreira, 2008;Leonardi, 2012), mas testes semelhantes também têm sido empregados em ambientes virtuais em experimentos com humanos, (Sturz, Bodily & Katz, 2009) e com cachorros (Martins-Filho, 2015).…”
Section: Isaac Newtonunclassified
“…Entretanto, avanços relativamente recentes no estudo da percepção olfativa, como o desenvolvimento da olfatometria e de aparelhos automatizados (olfatômetros), têm permitido o controle experimental dessas variáveis, possibilitando a implementação de procedimentos de treino de comportamento complexos com ratos e a obtenção de resultados inéditos com essa espécie (Slotnick & Schellinck, 2002). Por exemplo, as únicas demonstrações de learning set em ratos têm sido obtidas quando estímulos olfativos foram usados no treino discriminativo (Bailey, 2006;Slotnick, 1994;Slotnick, Hanford & Hodos, 2000) e a aprendizagem em tarefas de reversão de discriminação simples parece ser facilitada quando odores são usados como estímulos (Nigrosh, Slotnick & Nevin, 1975).…”
Section: Modalidades Em Procedimentos De Discriminação De Estímulosunclassified